ANALISIS MUTASI PINDAH PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH PROVINSI SULAWESI SELATAN - Riana Kasiran (Jurnal Administrasi Negara, 2021)
Mutation is the transfer of civil servants from outside agencies to to South Sulawesi provincial government agencies for certain reasons. This study aims to determine and analyze the reasons for the transfer of Civil Servants to the South Sulawesi provincial government. There are 46 informants. The approach used is a qualitative approach, especially case studies using questionnaires, interviews, observations, and document review.The results of the study indicate that mutation in the South Sulawesi provincial government include horizontal mutations, carried out based on existing guidelines, and the principle of the merit system. However, under certain conditions, mutations are carried out based on a spoil system. Some of the obstacles faced were: the absence of a time standard; the existence of a moratorium; readiness of the originating agency to release and the intended agency to receive it; routine office activities that are still ongoing; the Covid-19 pandemic; and natural disasters. Description of reasons for mutation: mutation at the employee's own wish and Productive Task Transfer. Transfer of his own volition: in his original institution, his duties and fields of work are not in accordance with his job; at the institution of origin, the work environment is not in accordance    with his physical condition or health reasons; want to develop a career; return to the area of ​​origin/close to the family: follow the figure of the leader; get better benefits. Transfer of Productive Tasks (ATP), namely the reasons proposed by the leadership as an effect of the election of Regional Heads in South Sulawesi.